Адаптивний електротепловий захист напівпровідникових перетворювачів - Baraniuk, R. A.; Todorenko, V. A.; Bondarenko, O. F. (PE "Politekhperiodika", Book and Journal Publishers, 2017)
Thermal management for power converters during normal operation and transient modes when electrical components are warmed up is an actual problem. This can be particularly important for converters with intermittent duty operation, e.g. power supplies for resistance welding. According to some research, nearly 60% of failures are temperature-induced, and for every 10°C temperature rise in operating environment the failure rate nearly doubles.In this paper, thermal motion of state equations eigenvalue is analysed. It is shown, that in semiconductor converters with an output smoothing filter it is appropriate to use thermal protection devices based on thermal normalisation of the converter filter and, while for cases when short circuits are possible it is appropriate to use a soft start system with thermal adaptation for soft start time factor.Based on these results, two systems of thermal protections operating for semiconductor power converters are introduced. Simulation of combined electromagnetic and thermal processes in buck converter operating with both thermal management systems in overlapping environments MATLAB/Simulink and PLECS showed the possibility to significantly reduce thermal shock on semiconductor components. Using the system of filter parameters normalisation decreases the temperature of the crystal from 210°C to 85°C, using the adaptive soft start system decreases the temperature from 180°C to 80°C. The simulation results are confirmed by tests on real devices.